Selected factors associated with primary sub fertility and it's consequences - Herath, I.N.S (My University, 2011)
A pre-tested questionnaire was used to get the details of socio demographic characteristics and use of contraceptives. Data extraction from was used to get details about the causes of primary sub fertility identified, from the clinic records. The psychological distress state of the female was assessed using General Health Questionnaire 12 ( GHQ-12) . In the study group more than 82 percent of the couples were from urban areas with a mean age of 29.6 years for females and 32.6 years for males. The mean age at marriage for females was 26.4 years and the mean duration of marriage was 3.5 years for this sample. When the use of hormonal contraceptives was considered, about 14 percent newly married females have used this method to delay their first pregnancy . Another 12 percent have used condoms or some other traditional method for this purpose. Mean duration of use of a contraceptive method was nine moths and for hormonal contraceptives, it was only eight months. It was revealed that about 25 percent of the females who attend the subfertility clinics were psychologically distressed